Technological Developments on Solar Cell Production and Tendencies - (:unkn) unknown (WORLD SCIENTIFIC AND ENGINEERING ACAD AND SOC, 2008)
The increasing energy demand and decrease in conventional energy resources orientates researches to be in tendency to continuously increase the output of alternative energy resources. The solar cells are very important in such alternative resources. In this study, notable performance properties of solar cells are examined and fields that may be oriented to for future researches are studied. Using of nanotechnologies in hybrid solar cell design can decrease costs by increasing the output of PV cell and modules. The nanotechnology is discussed by considering its three key fields in new options perspective in basic principles, mechanisms and clean energy production. Photovoltaic cell production tendencies and costs are also examined.
Keywords: Solar cell; nanotechnology; nanotube; quantum dots; hot carrier; cost; NANOMATERIALS